Follow the steps to solve the equation using the algebra tiles.

−4x + 1 = x + (−4)

1. Add 4 positive x-tiles to both sides and create zero pairs.

2. Add 4 positive unit tiles to both sides and create zero pairs.

3. Divide the unit tiles evenly among the x-tiles.

x =

1 answer

To solve the equation \(-4x + 1 = x + (-4)\) using algebra tiles, follow the steps given:

Step 1: Add 4 positive x-tiles to both sides and create zero pairs.

Starting equation: \[ -4x + 1 = x - 4 \]

Adding 4 positive x-tiles to both sides: \[ -4x + 4x + 1 = x + 4x - 4 \]

This simplifies to: \[ 0 + 1 = 5x - 4 \] which is: \[ 1 = 5x - 4 \]

Step 2: Add 4 positive unit tiles to both sides and create zero pairs.

Next, add 4 positive unit tiles to both sides to eliminate \(-4\): \[ 1 + 4 = 5x - 4 + 4 \]

This simplifies to: \[ 5 = 5x \]

Step 3: Divide the unit tiles evenly among the x-tiles.

Now, divide the unit tiles by the number of x-tiles: \[ \frac{5}{5} = x \]

This gives you: \[ x = 1 \]

So the solution to the equation is: \[ \boxed{1} \]